A critical review of the article: Mathematical modelling of the biofiltration treating mixtures of toluene and N-propanol in biofilm and gas phase - Nicolas Guerrero Chavez; Gilberto González Gómez; Karla Anhel Camarillo Gómez (Entreciencias: Diálogos en la Sociedad del Conocimiento)
In this review, the paper of Shuguang Li et al. in 2023 is analyzed, where it empathized the results obtained in gas phase simulation for n-propanol and toluene. Therefore, a comparison between these results with the papers of Sivakumar et al. (2015), Dharmalingam et al. (2020), and Salomi et al. (2021) was established, concluding that all the contributions have the same solution method with different mathematical models, and reported similar results between them. The common method of solution is the homotopy perturbation method for the solution of nonlinear equations.